Microwave and millimeter-wave electronic packaging - Sturdivant, Rick (Artech House microwave library., 2014)
Presenting the packaging issues which are unique to microwave and millimeter-wave frequencies, this book reviews lower frequency packaging techniques and how they can be tailored or analyzed for higher frequency designs. --